'Cognitive aging' in teachers: L2 teachers' cognitive performance across various stages in their teaching career. Issue 4 (2nd October 2019) - Karimi, Mohammad Nabi; Norouzi, Monireh
ABSTRACT: Reconceptualization of teaching as a thoughtful process guided by teachers' thinking has inspired a substantial body of research into various factors involved in shaping teachers' cognitions. Experience has been cited as one of the factors structuring teachers' cognitions. However, despite the multitude of studies comparing the cognitions underlying novice and experienced teachers' performance, there is little evidence, if any, as to how teacher cognition might vary across various levels of teaching experience. Therefore, this study aims to address this gap by comparing the pedagogical thought units of teachers at different stages of their teaching career. Twenty teachers were assigned to five groups of varied teaching experience ( n  = 4 per group). Teachers' class performances were video recorded and stimulated recall technique was used to probe into their pedagogical reasoning. The analyses of the data revealed significant differences across the five groups both in the sums of frequencies of pedagogical thought units produced by the teachers and in a number of the dominant pedagogical thought categories. The results also point to the more noticeable role of experience in (re)structuring teachers' cognitions in the initial years of teaching and declines in its influence at later stages of the teaching career.